The Effects of Electronic Storybook on EFL Students' Reading Performance - Awaludin Rizal; Ridayani; Safrudin Sahmadan; Ali Ajam (Prosiding Seminar Nasional Pendidikan FKIP Universitas Lampung, 2024)
This study investigated the effect of electronic books on EFL students Reading performance. A quantitative study with a quasi-experimental design was implemented through applying electronic books as instruments. The study adopts a pre-post control group design where each twenty students were randomly assigned to either a control or an experimental group. Students of the experimental group were instructed by using electronic books approach, whereas, the control group received traditional treatment such as grammar translation method. The study results showed that using the electronic storybook on EFL students can significantly raise students' reading performance, with a discernible difference in effectiveness between the experimental and control groups. The study sheds lighter on the value of using electronic books to promote reading performance in an EFL classroom. Additionally, the study makes recommendations for EFL teachers on how to make the application of this method in their lesson plans more effective.